Effect of pH on the static adsorption of foaming surfactants on Malaysian sandstone - Mushtaq, M. (Springer Verlag, 2015)
Adsorption of surfactants on the reservoir rock is one the most important factors which decide the economic feasibility of recovery process. This study reports the adsorption of two in-house developed CO2-philic foaming surfactants on Malaysian sandstone. The point of zero charge (PZC) of the rock sample was determined to be 8.13. The surfactants contained single tail (FS-1) and two tails (FS-2) in their structures. Static adsorption tests were conducted as traditional bottle test as well as during the foam test experiments. For the bottle tests, it was noted that the FS-2 underwent more adsorption (4.94Â mg/g) when compared to FS-1 (4.32Â mg/g). The pH effect was significant, and at low pH value (pH 6), the adsorption was almost five times more for both surfactants when compared to the adsorption at high pH (pH 10) conditions. During the foam test at pH 6, the adsorption results for FS-1 and FS-2 were 4.02 and 4.48Â mg/g, respectively. The effect of increasing the pH to 10 was comparable to bottle test results, and adsorption was decreased about five times. The bottle test gave slightly high adsorption values primarily because the contact time was longer (24Â h) when compared to foaming test adsorption values where time is only about 30Â minutes. In foaming tests, sparging of CO2 gas enhanced the shear mixing of contents thereby increasing the adsorption degree resulting in the similar adsorption values despite of less contact time. The study revealed that the adsorption of surfactant depends on many parameters, and one way of effective control is to adjust the pH of the fluid higher than the PZC of the rock. Â© 2015, Saudi Society for Geosciences.